Предмет:
МатематикаАвтор:
cupcakersa9х²+4х=у²+3
(х+2)²-4-у²=3
(х+2-у)(х+2+у)=7
1. (х+2-у)=7; (х+2+у)=1⇒2х+4=8; х=2,у=1-2-х=--3. (2;-3)
2. (х+2-у)=1; (х+2+у)=7⇒2х+4=8, х=2, у=7-х-2=3, (2;3)
3. (х+2-у)=-1; (х+2+у)=-7; 2х+4=-8; х=-6; у=-7-2-х=-3, (-6;-3)
4. (х+2-у)=-7; (х+2+у)=-1; 2х+4=-8; х=-6, у=-1-2-х=3. (3;-6)
Автор:
stellapygqДобавить свой ответ
Предмет:
ФизикаАвтор:
kokolarsenОтветов:
Смотреть
Предмет:
МатематикаАвтор:
rosieaaxsОтветов:
Смотреть
Предмет:
ГеометрияАвтор:
lamontarcherОтветов:
Смотреть